Inhibition of the NF-κB pathway as a candidate therapeutic strategy for cryopyrin-associated periodic syndrome. Issue 3 (May 2014) - Shimogaki, Satoka; Ito, Sayaka; Komatsu, Sachiyo; Koike, Ryuji; Miyasaka, Nobuyuki; Umezawa, Kazuo; Kubota, Tetsuo
Abstract Objectives. Cryopyrin-associated periodic syndrome (CAPS) is caused by unrestricted IL-1β release due to mutation of the gene coding NLRP3. This study aimed to clarify whether NLRP3-related IL-1β release is dependent on the NF-κB pathway. Methods. Peripheral blood mononuclear cells (PBMCs) from healthy subjects or patients with Muckle–Wells syndrome were primed with LPS and subsequently stimulated by ATP. Human umbilical vein endothelial cells (HUVECs) were cultured with the supernatant obtained from LPS-plus ATP-stimulated PBMCs. Expression of proinflammatory molecules was estimated using RT-PCR, ELISA or immunochemical staining, in the presence or absence of an NF-κB inhibitor (−)-dehydroxymethylepoxyquinomicin (DHMEQ). Results. DHMEQ inhibited expression of proIL-1β and NLRP3 by normal PBMCs primed with LPS, resulting in inhibition of caspase-1 activation and IL-1β secretion by the cells after subsequent stimulation with ATP. DHMEQ also inhibited expression of IL-1β, TNFα, IL-6 and VCAM-1 by HUVECs. Patient cells released IL-1β spontaneously or by ATP-stimulation even without LPS-priming. Both the spontaneous and stimulated IL-1β releases were inhibited by DHMEQ without affecting viability of the cells. Conclusions. These results clearly indicate that IL-1β production through the NLRP3 inflammasome is dependent on the NF-κB pathway, which could be a good target for the development of a novel therapeutic strategy for CAPS.